Individual-Cell Monitoring System in Energy Backup Banks - Ortega-Sanchez, Cesar (IEEE, 2004)
This paper presents the characteristics of a lowcost individual-cell monitoring system suitable for batterybased backup systems. The system is being developed at the Department of Control and Instrumentation (GCI), Institute of Electrical Research (IIE), Mexico. The system has three main components: a central unit that stores, analyses and presents cells data, a data concentrator module that gathers data and sends it to the central unit and multiple data acquisition modules, one for each monitored cell. The concentrator can also work as a low-cost charge-controller for lead-acid batteries connected to photovoltaic panels. This paper also presents results from the field tests applied to thecharge controller.